Dynamic Vesicles Formed By Dissipative Self‐Assembly. Issue 1 (7th November 2019) - Wanzke, Caren; Jussupow, Alexander; Kohler, Fabian; Dietz, Hendrik; Kaila, Ville R. I.; Boekhoven, Job
Abstract: Synthetic lipid membranes have served as important models for cellular membranes. However, these static membranes do not recapitulate the dynamic nature of the biological membranes which are frequently remodeled to support cellular function. An ideal membrane model would thus also display dynamic exchange of lipids. In this work, we achieve such a system by coupling the self‐assembly of peptides into membranes with a chemical reaction cycle. The reaction cycle activates and deactivates the peptides for self‐assembly at the expense of a chemical fuel. The resulting membranes are dynamically remodeled, and, over their 40 min lifetime, they emerge, grow, and are torn apart before they eventually decay. Abstract : Keep it moving : The self‐assembly of peptides into vesicles is coupled to a dynamic chemical reaction cycle. These vesicles emerge in response to fuel, and continuously remodel and decay when all fuel is depleted.